Utilização das fichas de registro de vacinações pelos centros de saúde na Divisão Regional de Saúde de Campinas, Estado de São Paulo, Brasil The use of the vaccination record cards by the local health centers of the Campinas Regional Health Division of the State of S. Paulo, Brazil - William Moffitt Harris (Universidade de São Paulo, 1974)
Foi descrito um levantamento amostral comparativo analítico referente à coincidência de dados encontrados nas cadernetas de vacinações (amarelas) pertencentes a crianças e as fichas de registro (azuis) pertencentes aos arquivos dos Centros de Saúde. Este levantamento foi feito em 16 municípios com mais de 30 mil habitantes da Região Administrativa de Campinas, Estado de São Paulo, que demonstrou haver em 788 cadernetas efetivamente examinadas, 2.307 anotações divergentes referentes a vacinas. Apenas 386 (48,9%) cadernetas amarelas coincidiam perfeitamente com as respectivas fichas azuis de registro. Tornou-se evidente que os arquivos de fichas de registro de vacinações dos Centros de Saúde não oferecem condições para uma eficiente avaliação da cobertura vacinal da população. A comparative analytical sample survey regarding the coincidence of data found in Vaccination Record Cards (yellow ones) belonging to children and those (blue ones) belonging to the local Health Units' archives conducted in 16 counties with populations over thirty thousand among those pertaining to the Campinas Administrative Region (83 counties with a total population of 2.3 million) of the State of S. Paulo, Brazil, was here described showing that in 788 cards effectively examined there were 2,307 diverging vaccine informations. Only 386 (48.9%) Yellow Cards coincided perfectly with their corresponding Blue Cards. It became quite obvious that the vaccination archives of the local Health Units do not yield conditions for an efficient vaccinal coverage evaluation of the population.